Neutrophil-to-Lymphocyte Ratio (NLR) as An Inflammation Degree Marker in Tongue Cancer Patient - Syakira Husna Lathifah; Winny Yohana; Moch. Rodian (Jurnal Kesehatan Gigi, 2021)
Tongue cancer is one of the most common malignancies of all oral malignancies. Cancer staging is induced by a systemic inflammatory response with one of the markers, one of them is neutrophil-lymphocyte ratio (NLR). This study aims to provide an overview of the NLR as a marker of the degree of inflammation in patients with tongue cancer. This systematic literature review was conducted online from January 2021 to March 2021 against articles reporting RNL as a marker of inflammatory action in patients with tongue cancer. The search for articles referred to Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) and conducted through PubMed, PMC, ScienceDirect, and EBSCOhost with the publication year 2015-2020. Selected articles met the criteria according to the PICO framework (Population, Intervention, Comparison, Outcome). Article screening is done by reading the title and abstract, checking for duplication, and reading the entire text. Sixteen in 841 research articles with observational study design were identified, the NLR cut-off value ranges from 2.04-2.95. Nine in ten research articles suggested a relationship between the NLR value and several clinicopathological characteristics of the patient. Twelve articles mentioned that there was the association of RNL with patient overall survival (OS), disease-free survival (DFS), and disease-specific survival (DSS). The NLR value can be an indicator of the degree of inflammation in patients with tongue cancer as assessed from the parameters of the clinicopathological assessment and can be a predictive factor for patient's prognosis or survival status.